PENGALAMAN KOMUNIKASI PENDAMPING DENGAN ANAK DISABILITAS MAJEMUK DI YAYASAN SAYAP IBU BINTARO - Prihandhini, Lauditta Nurseptia; Hadisiwi, Purwanti; Prasanti, Ditha (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2020)
This study aims to determine the experience of care giver communication with multiple disability children in the Sayap Ibu Bintaro Foundation; (1) care giver motives in the Sayap Ibu Bintaro Foundation; (2) care giver's self-meaning at the Sayap Ibu Bintaro Foundation; (3) use of care giver verbal and non verbal communication with multiple disability children. This study uses a qualitative method with a phenomenological approach and uses symbolic interactionalism theory. Data collection techniques used in this study were in-depth interviews and observations. The results of this research show that (1) a person's motives for being a care giver are divided into causes, namely: (a) getting invitations from others to cause empathy; and (b) compassion. the motives of the goal are (a) gain experience, and (b) develop abilities. (2) The meaning of self-companion is to be a parent for a child with multiple disabilities. (3) While the use of verbal communication that is often used by care giver is to provide motivation and provide advice to children with multiple disabilities, and the use of non-verbal communication used by care giver with making gestures or body language while communicating with multiple disability children in the Sayap Ibu Bintaro Foundation (YSIB)